Functions of Bombyx mori cathepsin L-like in innate immune response and anti-microbial autophagy. (March 2021) - Sun, Yu-Xuan; Chen, Chen; Xu, Wen-Jie; Abbas, Muhammad Nadeem; Mu, Fang-Fang; Ding, Wen-Jing; Zhang, Hai-Jun; Li, Jun
Abstract: Cathepsins belongs to the cysteine protease family, which are activated by an acidic environment. They play essential biological roles in the innate immunity and development of animals. Here, we identified a 62 kDa cathepsin L-like protease from the silkworm Bombyx mori. It contained putative conserved domains, including an I29 inhibitor domain and a peptidase C1A domain. The expression analysis revealed that cathepsin L-like was highly produced in the fat body, and 20-hydroxyecdysone (20 E) induced its expression. After challenge with three different types of heat-killed pathogens ( Escherichia coli, Beauveria bassiana, and Bacillus cereus ), the mRNA levels of cathepsin L-like significantly increased and displayed variable expression patterns in the immune tissues, suggesting its potential role in the innate immune response. The suppression of cathepsin L-like altered the expression of immune-related genes associated with the Toll and IMD pathway. Besides, autophagy-related genes such as Atg6, Atg8, VAMP2, Vps4, and syntaxin expression were also altered, indicating that cathepsin L-like regulates innate immunity and autophagy. Fluorescence microscopic analysis exhibited that cathepsin L-like was localized in the cytoplasm, and it was activated and dispersed throughout the cytoplasm and nucleus following the induction of anti-microbial autophagy. Altogether, our data suggest that cathepsin L-like may regulate the innate immune response and anti-microbial autophagy in the silkworm, B. mori . Highlights: A cathepsin L-like protease was characterized from Bombyx mori for the first time. Cathepsin L-like expression increased following 20 E treatment and pathogens challenge. Cathepsin L-like RNAi changed the expression patterns of immune and autophagy-related genes. Cathepsin L-like was activated after the induction of autophagy by rapamycin and LPS.